Outskirts : queer experiences on the fringe - Compton, D'Lane R. (D'Lane Rebecca), 1977-; Stone, Amy L. (New York University Press, 2024)
"Outskirts is an edited volume from sociology scholars that addresses the complexity of the queer experience in diverse spaces, places, and identities in the United States"-- Provided by publisher.
Keywords: Gay people -- United States -- Social conditions.; Sexual minorities -- United States -- Social conditions.; Minorités sexuelles -- États-Unis -- Conditions sociales.; SOCIAL SCIENCE / LGBT Studies / Gay Studies.; United States.; LGBTQ+ people.; LGBTQ+ social processes.; Society & culture: general.; Family and Relationships.; LGBTQ+ Interest.